Understanding the dimensions and dynamics of poverty in underserved settlements in Colombo - Gunetilleke, Neranjana; Cader, Azra Abdul; Fernando, Myriam; Centre for Poverty Analysis (Sri Lanka); Colombo (Sri Lanka) (Colombo : Centre for Poverty Analysis, 2004)
Study on poverty in underserved settlements in Colombo by Colombo Municipal Corporation and Centre for Poverty Analysis, Sri Lanka.
Keywords: Poor -- Sri Lanka -- Colombo; Poverty -- Sri Lanka -- Colombo